DETERMINANTS OF INNOVATION DEVELOPMENT IN THE AGRI-FOOD SECTOR - Котвицька, Наталія Миколаївна (Journal of Strategic Economic Research, 2023)
The agro-food sector plays an important role in the sustainable development of a country by providing food for the population and being one of the key economic sectors. However, in order to ensure the sustainable development of the agro-food sector, it is necessary to provide it with an innovative potential. This article examines and investigates the determinants of innovation development in the agro-food sector and their impact on the economic growth of this industry. The importance of innovation for the agro-food industry is clear, as they can improve the quality of products, increase their production, and reduce production costs. Various aspects of innovation development in this sector are analyzed, including technological processes, marketing, management, and resource provision. The role of state policy in supporting innovation development in the agro-food sector is investigated, such as funding programs and incentives for enterprises that implement innovation, the development of the education system and scientific centers that conduct research in the field of agro-industrial complex. The research results have shown that the most important determinants of innovative development in the agricultural sector are technological development, investment, scientific research activity, human capital development, and marketing. It has been established that innovative development in the agricultural sector has a significant impact on the economic development of this industry, which in turn has a positive effect on the economy as a whole. However, it is worth noting that the innovative development in the agricultural sector is associated with significant challenges, such as insufficient funding, inadequate informational support, as well as the complexity of introducing new technologies in the sector, which may require changes in traditional production practices. The article aims to determine which determinants of innovative development in the agricultural sector are the most important and how they affect the growth of the economy in this industry.